2017
DOI: 10.1107/s2059798317013043
|View full text |Cite
|
Sign up to set email alerts
|

Conformational dynamics of the essential sensor histidine kinase WalK

Abstract: Two-component systems (TCSs) are key elements in bacterial signal transduction in response to environmental stresses. TCSs generally consist of sensor histidine kinases (SKs) and their cognate response regulators (RRs). Many SKs exhibit autokinase, phosphoryltransferase and phosphatase activities, which regulate RR activity through a phosphorylation and dephosphorylation cycle. However, how SKs perform different enzymatic activities is poorly understood. Here, several crystal structures of the minimal catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 56 publications
5
19
0
Order By: Relevance
“…HK853 structures reported here and the previously deposited in the PDB show that His260 side chain interact with the main chain oxygen of residue at position −4 (A256 in HK853) when adopts the gauche− rotamer. Similar interactions are observed for the phosphorylatable His in the CpxA (PDB 4BIX) 8 , WalK (PDB 5C93) 17 , VicK (PDB 4I5S) 20 , and PhoR (PDB 5UKV) 21 HKs, supporting that this interaction would be stabilizing the rotamer disposition. Close inspection of the His260 in the HK-RR pHs structures showed that this residue was also interacting with a sulfate ion through its side-chain Nε (Fig.…”
Section: Hk853-rr468 Structures Show a Ph Independentsupporting
confidence: 57%
See 1 more Smart Citation
“…HK853 structures reported here and the previously deposited in the PDB show that His260 side chain interact with the main chain oxygen of residue at position −4 (A256 in HK853) when adopts the gauche− rotamer. Similar interactions are observed for the phosphorylatable His in the CpxA (PDB 4BIX) 8 , WalK (PDB 5C93) 17 , VicK (PDB 4I5S) 20 , and PhoR (PDB 5UKV) 21 HKs, supporting that this interaction would be stabilizing the rotamer disposition. Close inspection of the His260 in the HK-RR pHs structures showed that this residue was also interacting with a sulfate ion through its side-chain Nε (Fig.…”
Section: Hk853-rr468 Structures Show a Ph Independentsupporting
confidence: 57%
“…2). Finally, we looked for the presence of a sulfate ion coordinated to the phosphorylatable His in other structures of HisKA family and we found that WalK (PDB 5C93), which was crystalized in presence of high concentration of sulfate (1.0 M ammonium sulfate) 17 , coordinated a sulfate ion in an equivalent position as HK853. In WalK the phosphorylatable His (His386) presented both trans and gauche− rotamers but the sulfate ion was coordinated to the gauche− rotamer ( Supplementary Fig.…”
Section: Gauche-transmentioning
confidence: 99%
“…7c), which would be sterically incompatible with an analogous motion of α1 of the other subunit. This has been discussed and analyzed thoroughly by 15 Bhate and coworkers 6 and corroborated by the recent structure and modelled dynamics of WalK 25 .…”
Section: Discussionsupporting
confidence: 54%
“…7C), which would be sterically incompatible with an analogous motion of α1 from the other subunit. This has been discussed and analyzed thoroughly by Bhate et al (9) and corroborated by the recent structure and modeled dynamics of WalK (35). The DHp domain of ShkA belongs to the major HisKA pfam family (36) that exhibits a HxxxxP motif (Fig.…”
Section: Discussionmentioning
confidence: 53%